Numerical investigations on the optimal tool temperature distribution for the integrated manufacturing of hybrid structures. (November 2021) - Winter, Benjamin; Demes, Michael; Hürkamp, André; Dröder, Klaus
Abstract: The combination of hot-stamped steels and fibre-reinforced thermoplastics (FRTP) offers great potential for lightweight design. The process steps of hot stamping and thermoforming for the manufacturing of such hybrid structures are usually carried out in two separate steps. After hot stamping, the blank has to be reheated for the application of FRTP in order to enable the bonding of FRTP to the blank. Process integration of the individual processes means that reheating of the blank during thermoforming is no longer necessary. Due to non-uniform contact conditions during hot stamping between blank and tool, an inhomogeneous temperature distribution in the blank occurs, which would lead to non-uniform bonding properties between blank and FRTP after thermoforming. The aim of this work is to determine this non-uniform contact and the resulting heat transfer by a numerical model. By segmenting the tool in the model, a possibility is shown to control the non-uniform contact and to achieve a homogeneous temperature distribution in the blank after hot stamping. Furthermore, the temperature adaptability of the used tool and the resulting temperature distribution in the blank is investigated. Finally, the manufactured structures are tested in a numerical three-point bending test in order to be able to make a statement about their performances.